Clinical Factors Associated With Response to Fecal Diversion in Crohn's Disease. Issue 10 (5th November 2020) - Buhulaigah, Hassan; Truong, Adam; Zaghiyan, Karen; Fleshner, Phillip
Up to 80% of Crohn's disease (CD) patients require surgery. Fecal diversion is used selectively in CD proctocolitis refractory to medical treatment or advanced perianal disease. This study examines associations between clinical features in predicting clinical response (CR) to fecal diversion in CD. Charts of CD patients undergoing fecal diversion for medically refractory disease or perianal disease were reviewed. Clinical response was assessed focusing on improvements in urgency, abdominal and perineal pain, decreased anal fistula drainage, and weight gain. Univariate binary logistic regression and multivariate forward-stepwise modeling analysis were used to determine associations with CR. The study cohort comprised 79 patients. After a median follow-up of 36 (3-192) months, 40 (51%) patients achieved a CR. Binary logistic regression analysis revealed both age at diagnosis (hazard ratio [HR] 1.05; confidence interval [CI] 1.01-1.09; P = .007) and disease duration (HR .91; CI .86-.96; P = .001) to be significantly associated with CR. Later age of onset (HR 1.05; CI 1.01-1.10; P = .002) and shorter disease duration (HR .91; CI .86-.97; P = .02) remained significant on multivariate analysis. This largest reported series of fecal diversion for refractory CD in the biologic drug era revealed that young age at diagnosis and long disease duration are associated with a lower CR.